Construction of recombinant Pichia pastoris strains for ammonia reduction by the gdhA and glnA regulatory genes in laying hens - Kunxian Feng; Wei Wang; Jinsheng Rong; Juanboo Liang; Jiandui Mi; Yinbao Wu; Yan Wang (Ecotoxicology and Environmental Safety, 2022)
Ammonia emissions have become an important environmental challenge for the livestock industry. Probiotics are often used as additives to reduce ammonia, and the ammonia reduction efficiency of common probiotics is approximately 20–40%. In this study, we constructed a gdhA recombinant Pichia pastoris strain, glnA recombinant Pichia pastoris strain and gdhA-glnA Pichia pastoris recombinant strain using the gdhA and glnA genes, which have the potential function of reducing ammonia emissions. The results of in vitro fermentation showed that compared with the control, wild-type Pichia pastoris and pPICZA strains, the gdhA, glnA and gdhA-glnA recombinant strains significantly reduced ammonia emissions in laying hens (P < 0.05), with emission reduction efficiencies of 63.95%, 65.68% and 74.04%, respectively. The reason may be that the recombinant Pichia pastoris strains can convert ammonium nitrogen into amino acids for self-growth through ammonia assimilation, and reduce the pH, uric acid and urea content in the intestinal tract of livestock and poultry, and urease activity. Therefore, the construction of recombinant strains can provide technical support for reducing ammonia pollution in the livestock industry.